2022
DOI: 10.26509/frbc-wp-202237
|View full text |Cite
|
Sign up to set email alerts
|

What is the predictive value of SPF point and density forecasts?

Abstract: This paper presents a new approach to combining the information in point and density forecasts from the Survey of Professional Forecasters (SPF) and assesses the incremental value of the density forecasts. Our starting point is a model, developed in companion work, that constructs quarterly term structures of expectations and uncertainty from SPF point forecasts for quarterly fixed horizons and annual fixed events. We then employ entropic tilting to bring the density forecast information contained in the SPF’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Building on Adrian, Boyarchenko, and Giannone (2019), Adams, et al (2021) find evidence of downside risks in the densities of observed SPF forecast errors based on quantile regressions that condition on financial conditions. In companion work (Clark, Ganics, and Mertens, 2022), we investigate the value of conditioning fan charts on information contained in the SPF's density forecasts, which come in the form of fixed-event probability bins. That approach also connects to the works of Bassetti, Casarin, and Del Negro (2022), Clements (2018), Clements andGalvão (2017), andGanics, Rossi, andSekhposyan (2021); for a recent survey, see Clements, Rich, and Tracy (2022).…”
Section: Related Literaturementioning
confidence: 99%
“…Building on Adrian, Boyarchenko, and Giannone (2019), Adams, et al (2021) find evidence of downside risks in the densities of observed SPF forecast errors based on quantile regressions that condition on financial conditions. In companion work (Clark, Ganics, and Mertens, 2022), we investigate the value of conditioning fan charts on information contained in the SPF's density forecasts, which come in the form of fixed-event probability bins. That approach also connects to the works of Bassetti, Casarin, and Del Negro (2022), Clements (2018), Clements andGalvão (2017), andGanics, Rossi, andSekhposyan (2021); for a recent survey, see Clements, Rich, and Tracy (2022).…”
Section: Related Literaturementioning
confidence: 99%